Reproducibility of the Magnitude of Lens Rotation Following Implantation of a Toric Intraocular Lens with Modified Haptics - Quesada GA; Quesada RA; Jones JJ; Straker BJK; Zhao W; Tsai L; Vilupuru S (Clinical Ophthalmology, 2022)
Gabriel A Quesada,1 Rodrigo A Quesada,1 Jason J Jones,2 Benjamin JK Straker,3 Wuchen Zhao,3 Linda Tsai,3 Srividhya Vilupuru3 1Centro de Oftalmología y Cirugía Plástica, San Salvador, El Salvador; 2Jones Eye Clinic, Sioux City, IA, USA; 3Johnson & Johnson Surgical Vision, Inc, Irvine, CA, USACorrespondence: Srividhya Vilupuru, Johnson & Johnson Surgical Vision, 31 Technology Dr Suite 200, Irvine, CA, 92618, USA, Tel +1-949-581-5799, Email SVilupur@ITS.JNJ.comPurpose: To evaluate the reproducibility of magnitude of postoperative IOL rotation following implantation of a toric intraocular lens (IOL) with modified haptics, in comparison with a Proof-of-Concept (POC) study of prototype IOLs featuring the same haptic design.Patients and Methods: A post-market, prospective, multicenter, single-arm, open-label clinical study was conducted. TECNIS Toric II IOL (Johnson & Johnson Vision, Irvine, CA, USA, Models ZCU150 to 600) were implanted in 125 subjects and evaluated at 1-day and 1-week postoperatively. An objective photographic method was used to determine postoperative IOL rotation. Uncorrected distance visual acuity (UCDVA), postoperative astigmatism, and surgeon satisfaction were also assessed. Rotation data were compared to the POC study in which two prototype non-toric monofocal IOLs, one with the same haptic design as Model ZCU, were studied.Results: Mean absolute rotation was 0.82° ± 1.0° and 0.84° ± 0.92°at 1-day and 1-week visits, respectively. The percentage of eyes with ≤ 5° of absolute rotation was 98.9% and 99.5% at the 1-day and 1-week visits, respectively. The magnitude of rotation was similar to the POC study prototype IOLs. At 1-week, mean monocular UCDVA was 0.026 ± 0.135 (~20/21) logMAR and mean residual manifest refractive cylinder was 0.30 D ± 0.35 D. The mean signed axis difference (postoperative minus operative) of the TECNIS Toric II IOL was 0.23° ± 1.27° at 1-day and − 0.07° ± 1.25° at 1-week, indicating a clockwise drift. At 1-week, surgeons were very satisfied or satisfied with overall clinical outcomes and rotational stability in 98% of implanted eyes.Conclusion: The TECNIS Toric II IOL, with frosted, squared haptics, demonstrated low magnitude of postoperative IOL rotation, excellent uncorrected distance vision, and minimal residual astigmatism. The POC study design was supported, demonstrating that prototype non-toric monofocal IOLs can predict clinical performance of toric IOLs with the same haptic design.Keywords: toric IOL, astigmatism, IOL rotation, cataract, surgery, axis misalignment